Modelling the suppression of autoimmunity after pathogen infection. (3rd May 2018) - Oliveira, Bruno M. P. M.; Trinchet, Ricard; Otero Espinar, María Victoria; Pinto, Alberto; Burroughs, Nigel
Abstract : We study a mathematical model of immune response by T cells where the regulatory T cells (Treg) inhibit interleukin 2 (IL‐2) secretion. We model the suppression of the autoimmune line of T cells after a different line of T cells responded to a pathogen infection. In this paper, we show that if the population of the pathogen responding line of T cells becomes large enough, the competition for IL‐2 and the increase in the death rates may lead to a depletion in the concentration of autoimmune T cells. Provided this lasts for a sufficiently long time, the concentration of autoimmune T cells can be brought down to values inside the basin of attraction of the controlled state, and autoimmunity can be suppressed.